Phase-Field Models for Biofilms II 2-D Numerical Simulations of Biofilm-Flow Interaction (Communications in Computational Physics, 2008)
We study the biofilm-flow interaction resulting in biofilm growth, deformation and detachment phenomena in a cavity and shear flow using the phase fieldmodel developed recently [28]. The growth of the biofilm and the biofilm-flow interaction in various flow and geometries are simulated using an extended Newtonianconstitutive model for the biofilm mixture in 2-D. The model predicts growth patterns consistent with experimental findings with randomly distributed initial biofilmcolonies. Shear induced deformation, and detachment in biofilms is simulated in ashear cell. Rippling, streaming, and ultimate detachment phenomena in biofilms aredemonstrated in the simulations, respectively, in a shear cell. Possible merging of detached biofilm blobs in oscillatory shear is observed in simulations as well. Detachment due to the density variation is also investigated shedding light on the possiblebacteria induced detachment.